The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.icarus.2012.06.029
|View full text |Cite
|
Sign up to set email alerts
|

The vertical distribution of the Venus NO nightglow: Limb profiles inversion and one-dimensional modeling

Abstract: International audienceUltraviolet (UV) spectra of the δ (190-240 nm) and γ (225-270 nm) bands of the nitric oxide (NO) molecule have been measured on the nightside of the atmosphere of Venus with the Spectroscopy for Investigation of Characteristics of the Atmosphere of Venus (SPICAV) instrument on board Venus Express (VEX). Excited NO molecules on the nightside of the planet are created by radiative recombination of O(3P) and N(4S) atoms. The atoms are produced by photodissociation of CO2 and N2 molecules on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
(80 reference statements)
1
15
0
1
Order By: Relevance
“…These were detected by the International Ultraviolet Explorer (IUE) and the Pioneer Venus UV instrument as well as by the SPICAV instrument onboard Venus Express (Stiepen et al, 2012(Stiepen et al, , 2013. Another reaction is combination of excited state N atoms with CO 2 to form NO (below).…”
Section: Nitric Oxidementioning
confidence: 99%
“…These were detected by the International Ultraviolet Explorer (IUE) and the Pioneer Venus UV instrument as well as by the SPICAV instrument onboard Venus Express (Stiepen et al, 2012(Stiepen et al, , 2013. Another reaction is combination of excited state N atoms with CO 2 to form NO (below).…”
Section: Nitric Oxidementioning
confidence: 99%
“…In 2012, Stiepen et al . [] published results from a statistical study of the NO airglow based on a larger data set for the Northern Hemisphere from Gérard et al . [].…”
Section: Discussionmentioning
confidence: 99%
“…Analyses derived from the Venus Express data [ Gérard et al ., ; Royer et al ., ; Stiepen et al ., ] have shown that the NO emission peaks at a mean altitude of 113 km, with the NO airglow being observed in the 95 to 132 km range. The limb brightness was found to range between 5 kR and 540 kR and the scale height to be about 8 km.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all these cases, the measured horizontal wavelengths and phase velocities have been demonstrated to be comparable with GWs propagating at the considered altitudes [ Peralta et al ., , ]. Occasional secondary peaks, probably induced by GW propagations, were also observed above the main peak of the NO nightglow from SPICAV (Spectroscopy for Investigation of Characteristics of the Atmosphere of Venus) data [ Stiepen et al ., ]. The effect of planetary waves in the O 2 nightglow intensity fluctuation was investigated by Hoshino et al .…”
Section: Introductionmentioning
confidence: 99%